Characterization of SERS platforms designed by electrophoretic deposition on CVD graphene and ITO/glass - Fioravanti, Federico (2020)
Here, we perform electrophoretic deposition (EPD) to control the assembly of citrate-coated Au nanoparticles (NPs) on ITO/glass and graphene. Monolayer graphene is obtained by CVD and transferred to ITO/glass free of polymer. A quick surface-enhanced Raman scattering (SERS) test determined that the optimal platform consists of drop-casting methylene blue (MB) onto as-deposited Au NPs (600 s at 1.0 V) to achieve 150× signal enhancement. Therefore, we proceeded in the same manner and deposited Au NPs under identical EPD conditions on graphene/ITO/glass. Then, we tested both platforms by immersing into 0.3 mM MB solution and found similar SERS intensity on the graphene- and ITO-containing platforms after 10 min and 66 h, respectively, which clearly demonstrates the importance of the substrate. To characterize the platforms, linear scan voltammetry (LSV) and SEM were used for assigning the NPs? oxidation peaks to their corresponding areas on the image. We found good agreement with respect to the number of NPs per μm2 as measured by LSV and SEM. We observed that EPD on graphene leads to six-fold larger coverage than on ITO/glass. These Au NPs were mostly assembled in the form of agglomerates located on the defects of graphene. If those agglomerates are dissolved by anodic stripping, no SERS signal was found from the MB analyte. This also demonstrates that the platform can be reused for further deposition and SERS analysis. This work provides a simple and controllable method for the design of advanced SERS platforms.